Requirement-based testing of an automotive ECU considering the behavior of the vehicle - Lee, S. H.; Park, T. W.; Chung, K. H.; Choi, K. H.; Kim, K. K.; Moon, K. H. (International journal of automotive technology, 2011)
HILS (Hardware In the Loop Simulation) and RBT (Requirement-Based Testing) are widely used to evaluate the performance and reliability of automotive ECUs (Electronic Control Units). The HILS method is used to predict the behavior of ECU-installed vehicles and to evaluate the performance of ECU controllers. RBT evaluates whether the embedded system satisfies the pre-defined requirements. In this study, the behavior of a vehicle is regarded as a system requirement, and an embedded system test procedure that evaluates the system requirement is proposed. In particular, a new method is introduced, which integrates HILS with RBT. Using the proposed method, the behavior of an articulated vehicle equipped with an AWS (All Wheel Steering) ECU is evaluated with RBT software.